Points of Intersection Between Positive Law and Islamic Law in the Enforcement of Human Rights in Indonesia - Firmansyah Firmansyah; Raya Hidayat; Ahmad Sofian (Al-Mahkamah: Islamic Law Journal, 2025)
This study analyzes the intersection between positive law and Islamic law in upholding human rights in Indonesia, focusing on the differences and similarities between the two legal systems in regulating basic human rights, such as the right to life, the right to liberty, and the right to justice. This study employed library research, utilizing library data such as books, scientific journals, manuscripts, and other documents. The results show that positive law and Islamic law differ in several aspects, such as the definition and scope of basic human rights, but also share similarities in several aspects, such as the recognition and protection of basic human rights. This research contributes to the development of law and human rights in Indonesia and provides recommendations for improving human rights enforcement in Indonesia through harmonization of positive law and Islamic law.